Studi Komparatif Persaingan Bisnis Retail Modern dan Tradisional Ditinjau dari Keunggulan Bersaing - Ade Surya Pertiwi; Pristiyono Pristiyono; Muhammad Ali Al Ihsan (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this research is to analyze the effect of promotion strategy, product sales, store design and service excellence on competitive advantage in traditional and modern retail. The research method is explanation (explanation) with a quantitative approach. The research conducted in this study used a survey that collected information using a questionnaire through the Google form. The analytical method uses Partial Least Square (PLS). The basic population of this research is traditional and modern retail customers. In this study, non-probability sampling was used as the sampling method. The samples obtained in this study were 96 respondents. The results of the study show that the variable promotion strategy and excellent service have a positive effect on competitive advantage. Retail product variables and business layout do not affect competitive advantage. The higher the retail store implements promotional strategies and excellent service, the greater its competitive advantage, but the higher product differentiation and business layout of the retail store does not increase competitive advantage.